Geometric Optimization of Hybrid Ion Trap (Journal of Atomic and Molecular Sciences, 2014)
In this study we determined the effect of geometry of ring electrode on theoperation of a new ion trap with cylindrical ring electrode and hyperbolical end capelectrode. This model indicated how adjusting the geometric cell parameters couldreduce the impact of presence of higher order fields. Our work also illustrated thepossibility of improving other desired properties of a trap. For example we foundhow these adjustments could minimize the non-linear effects. We also noticed thepossibility of increasing the time of ion storage in a trap by the effect of one field in ahybrid ion trap. In this study we have obtained all of the equations of motion in a trapanalytically.